Strong magnetic field dependence of critical current densities and vortex activation energies in an anisotropic clean MgB2 thin film - Kim, J.; Haberkorn, N.; Nazaretski, E.; Paula, R. de; Tan, T.; Xi, X.X.; Tajima, T.; Movshovich, R.; Civale, L.; Haberkorn, Néstor (Elsevier, 2015)
Fil: Haberkorn, N. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina